Non-specific granulomatosis. Pro diagnosis case. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
Clinical data and histological examinations excluded a tumor pathology and showed chronic granulomatous inflammation. Chalaziosis was first suspected, but the progressive extension also very distant from the eye and the long duration ruled out this hypothesis. An exogenous cause was then hypothesized: bacteriological tests showed S. aureus and Streptococcus mitis but there was no response to antibiotics. The causal role of varicella-zoster virus, fungi and leishmania (1) was ruled out thanks to clinical and laboratory findings. We thought of the exceptional human telazosis, an infestation that mainly affects domestic and wild animals caused by nematodes of the genus Thelazia (2). Already described in some Italian regions such as Basilicata, it has as a carrier and intermediate host flies feeding on lacrimal secretions; however, the ophthalmologists ruled out the presence of worms in the eyelids.